Handbook of research on supply chain resiliency, efficiency, and visibility in the post- pandemic era - Ramakrishna, Yanamandra, 1966- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book explores diverse strategies for achieving capabilities related to supply chain resilience and to expand the existing body of knowledge in this area to help develop models, frameworks, and theoretical concepts related to supply chain resilience to enhance efficiency and improve the visibility of supply chain"--